"Why is it that all the Dangerous Children are Black From the Neighborhoods?": Critical Phenomenology of the Concept of Risk Among Adults Educated at Therapeutic Boarding Schools. Issue 1 (15th March 2021) - Frantsman‐Spector, Alin; Shoshana, Avihu
Abstract: This article is based on in‐depth interviews with Israeli adults who had been labeled in their childhood as being at risk and removed from their home to residential care settings (RCS) by court order due to their families' extreme poverty. In seeking their perspective, the present article addresses the pivotal question of how, as adults, they define, experience, and relate to the concept of "at‐risk children." The interviews revealed critical phenomenological readings of the notion of risk and the social institution of RCS. Analyzing the critical phenomenology of the interviewees offers research contributions concerning the study of the social construction of the concept of risk, its phenomenology, and the long‐term ramifications of labeling children as being at risk and of educating them in RCS. Highlights: ● Adults, labeled at‐risk as children and educated in residential care‐settings were interviewed ● Interviews revealed critical phenomenological readings of the notion of risk ● Research contributions include examining the social construction of the concept of risk ● Long‐term ramifications of typing children as at‐risk are discussed